Continuous wave terahertz spectrometer based on two DFB laser diodes - Wilk, Rafał (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
In this paper, a continuous wave (cw) spectrometer in the far infrared range is presented. Electromagnetic radiation is generated via photomixing phenomena and covers frequencies between about 50 GHz and 1.1 THz with resolution of about 10 GHz. The measured emission characteristics of different antenna types are compared to simulation results. Transmission measurements of Bragg structure for terahertz frequencies proved high spectral resolution of the spectrometer.
Optica Applicata, Vol. 40, 2010, nr 1, s. 119-127
Keywords: optyka; terahertz; continuous wave spectroscopy; Bragg structure